Sifat Machiavelli, Tekanan Ketaatan dalam Keputusan Etis: Keputusan Individu dan Kelompok - Sulistya Hapsari, Aprina Nugrahesthy; Situmeang, Aida Sari; Utami, Intiyas (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2018)
This research aims to test causality of obedience pressure, the Machiavellian character, and the ethical decision. It employs laboratory experiment with 2x2 between within-subject experimental designs. The respondents are 170 students as the representative of junior accounting staff. The independent variable is the ethical decision, and the dependent variables are Machiavellian character and obedience pressure. The result of this research shows that obedience pressure has causal effect on ethical decision. The Machiavellian characteristic gives a negative effect on the decision of the subject under high obedience pressure. Decision made under high obedience pressure and in group decision-making result in a higher ethical decision compared to the decision made individually. Whereas, the subject under low obedience pressure whether as an individual or a group experiences low ethical dilemma which results in ethical decision making.